Improving Healthcare Delivery to Patients With Coronavirus by Enhancing Digital Health Literacy of Healthcare Providers: Implications for Healthcare Policymakers - Mehdi Kahouei; Marjan Momeni; Shahrbanoo Pahlevanynejad; Fatemeh Rahaei; Mojtaba Soltani-Kermanshahi; Samira Sadat Yaghoobi (Mazandaran University of Medical Sciences, 2023)
Background: The immense assorted variety of data accessible through the Internet, containing unconfirmed pernicious data, can spread rapidly and misguide nursing and allied health staff (NAHS). False impressions among NAHS postpone controlling endeavors to deliver important treatment, lead to the quick spread of contamination in clinical settings, and put patients' lives in danger. This research aimed to assess the impact of NAHS digital health literacy and other determinants on their behaviors during the COVID-19 pandemic.  Methods: This study was conducted on allied health and nursing staff in healthcare organizations affiliated with Semnan University of Medical Sciences in Iran. Two valid questionnaires were used: Digital health literacy and preventive behaviors. Multiple logistic models were used to explain the relationship between one dependent binary variable and other variables.  Results: There were significant direct and positive relationships between digital health literacy (β=0.60; 95% CI, 1.35%-2.45%; P<0.001) and English language skills (β=2.29; 95% CI, 1.79%-54.03%; P=0.009) with preventive behaviors. Conclusions: Strengthening the digital health literacy of medical staff can help reduce the spread of COVID-19 infections in healthcare settings. It is proposed that policymakers and nursing informatics educators adjust e-health policies to advance digital health literacy in healthcare settings.